Association between Secretor status and Norovirus Infection among Children Under 5 years of Age in South-South, Nigeria - Osazuwa F; Hailey G. (Covenant Journal of Physical and Life Sciences, 2021)
Norovirus has been identified to constitute a key biological cause of gastroenteritis worldwide. This study aimed to determine the association between secretor status and norovirus infection among children under 5 years of age with diarrhea in Edo, Bayelsa and Delta States, South-South, Nigeria. Ethical approval was received from participating health institutions before inclusion of patients in this study. A total of 505 participants, consisting of 405 children with diarrhea and 100 apparently healthy children, who served as controls were included in this study. Stool specimens were collected from all participants and analyzed for norovirus using a rapid lateral flow immunoassay kit. Secretor was determined using commercial test kits La and Lb antisera. The overall prevalence of norovirus antigen among children with diarrhea was 18.5%. Secretors were found to significantly have higher prevalence of norovirus in Delta State (OR=0.165; 95% C.I, 0.0048, 0.5609; P=0.0039) when compared to non-secretors, but there were no significant association between norovirus infection and secretor status among subjects in Bayelsa and Edo States. Routine screening for norovirus infection among secretors with diarrhea should be a priority among subjects from Delta State.